Analisis Tingkat Kesehatan Laporan Keuangan pada PT Bank Syariah Mandiri Tbk. dengan Metode CAMEL Periode 2016 – 2020 - Muhammad Iqbal Surya Pratikto; Nisha Nor Rahmawati (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
The purpose of this research is to see and find out the level of the soundness of the financial statements at PT Bank Syariah Mandiri Tbk using the CAMEL method (Capital, Asset Quality, The method of data collection used in this research is the documentation of secondary data sources that have been collected and have been documented on the bank's official website in the form of existing financial reports. The results obtained in this study are CAR, ROA, and NI very healthy, NPF, ROE, FDR healthy, and PDN, BOPO quite healthy.